Development of a Paradigmatic Model of Fall Incident-Related Injuries Based on Comprehensive Data in Residential Construction Projects - Khoshkar, Esmaeil; Ghazi Moradi, Mostafa; Safehian, Majid (Management Strategies and Engineering Sciences, 2024)
Falls are a significant public health risk and a leading cause of both fatal and non-fatal injuries among construction workers worldwide. A more comprehensive understanding of the causal factors contributing to fall incidents is essential for preventing falls in the construction industry. However, there is no general review of causal factors in the existing literature. Given the importance of addressing accidents and incidents in the construction industry, this study aims to develop a paradigmatic model of injuries caused by fall incidents based on comprehensive data from the residential construction sector. The main objectives of this research include identifying the injuries and factors influencing falls in the construction industry, developing a model, and providing solutions to reduce fall risks. The research methodology is content analysis, using a qualitative approach. To extract the factors influencing fall risk management, the meta-synthesis approach is employed. For data analysis in the qualitative section, 110 codes were derived from 48 domestic and international articles that met the criteria for relevance and quality, which were then combined to present an overall view. Following coding and identification of new factors, validity was assessed using the fuzzy Delphi technique, with consultation from 15 experts in Tehran. After validation of the indicators, the paradigmatic model was developed, which illustrates that causal, contextual, and intervening conditions lead to the occurrence of incidents. Along with appropriate strategies, these factors can control or mitigate various consequences. These findings contribute to research on the causes of falls in construction, the development of engineering controls, policy-making, intervention design to reduce fall risks, and the improvement of research synthesis methods.